How Steel Plants Implement Air Pollution Control in China - Bao, Jiushi (2019)
Air pollution is a severe issue in China. The fog and haze weather in the major cities in China not only covered the blue sky but also impact people’s health. The primary source of air pollution that forms fog and haze are vehicles exhaust, residential coal firing, and industrial air pollution emission. Among them, the industrial air pollution emission contributes a substantial per cent and is challenging to control. This research focuses on air pollution emission from the steel manufacturing plants, which are the influential air pollution producers among all industries. Since China government released the Action Plan on Prevention and Control of Air Pollution policy in 2013, most of the steel plants positively response to change and reform on implementing the air pollution control while the results of air pollution control are still not satisfied due to the reappearance of fog and haze weathers. This research investigates and analyzes what the source of industrial air pollution is and what techniques, management, strategy are applied in operations to control the air pollution in steel plants based on the case studies of two representative Chinese steel plants. Additionally, interesting findings are identified about how regulation enforcement and technology development affect an enterprise at three levels of operations strategy.